The Complexity of Implementing Inclusive Education in Elementary Schools in Era 5.0: A Case Study - Ariesta Dwi Wulandari; Deni Setiawan (Postgraduate, University of Mataram, 2023)
Not all citizens have obtained educational services fairly and equitably, especially those with certain limitations. This research provides an overview of the implementation of inclusive education that can reach all citizens without paying attention to the weaknesses and shortcomings of students in schools.Â This activity is descriptive qualitative research with source triangulation analysis. Descriptive qualitative research is in the form of research with a case study method, or approach carried out at Ummul Quro Elementary School, Semarang City. The results showed the criteria for children with special needs, special and regular student learning activities, the implementation of inclusive education by teachers,Â and the condition of students with special and regular needs in schools in the 5.0 era